Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

Differentiating between viruses and virus species by writing their names correctly - Francisco Murilo Zerbini; Stuart G. Siddell; Arcady R. Mushegian; Peter J. Walker; Elliot J. Lefkowitz; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Bas E. Dutilh; María Laura García; Sandra Junglen; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Genetic basis of inosine triphosphate pyrophosphohydrolase deficiency - Satoshi Sumi; Anthony Marinaki; Monica Arenas; Lynette Fairbanks; Monsor Shobowale-Bakre; David Rees; Swee Thein; Azhar Ansari; Jeremy Sanderson; Ronney De Abreu; Anne Simmonds; John Duley (Human Genetics, 2002)

Accumulation of plasma N-methyl-2-pyridone-5-carboxamide in patients with chronic renal failure - Ewa M. Slominska; Ryszard T. Smolenski; Marek Szolkiewicz; Neil Leaver; Boleslaw Rutkowski; H. Anne Simmonds; Julian Swierczynski (Molecular and Cellular Biochemistry, 2002)

Adenoviruses Encoding HPRT Correct Biochemical Abnormalities of HPRT-Deficient Cells and Allow Their Survival in Negative Selection Medium - Thomas D. Southgate; Derek Bain; Lynette D. Fairbanks; Adrian E. Morelli; Adriana T. Larregina; H. Anne Simmonds; Maria G. Castro; Pedro R. Löwenstein (Metabolic Brain Disease, 1999)